A Bis(silylenyl)pyridine Zero-Valent Germanium Complex and Its Remarkable Reactivity - Zhou, Yu-Peng; Karni, Miriam; Yao, Shenglai; Apeloig, Yitzhak; Driess, Matthias (Angewandte Chemie International Edition, 2016)
The synthesis, reactivity, and electronic structure of the unique germylone iron carbonyl complex [SiNSi]Ge0→Fe(CO)4 is reported. The compound was obtained in 49 % yield from the reaction of the bis(N‐heterocyclic silylenyl)pyridine pincer ligand SiNSi (1,6‐C5NH3‐[EtNSi(NtBu)2CPh]2) with GeCl2⋅(dioxane) to give the corresponding chlorogermyliumylidene chloride precursor [SiNSi]GeIICl+ Cl−, which was further reduced with K2Fe(CO)4. Single‐crystal X‐ray diffraction analysis of [SiNSi]Ge→Fe(CO)4 revealed that the Ge0 center adopts a trigonal‐pyramidal geometry with a Si‐Ge‐Si angle of 95.66(2)°. Remarkably, one of the SiII donor atoms in the complex is five‐coordinated because of additional (pyridine)N→Si coordination. Unexpectedly, the reaction of [SiNSi]Ge→Fe(CO)4 with GeCl2⋅(dioxane) (one molar equivalent) yielded the first push–pull germylone–germylene donor–acceptor complex, [SiNSi]Ge→GeCl2→Fe(CO)4 through the insertion of GeCl2 into the dative Ge0→Fe bond. The electronic features of the new compounds were investigated by DFT calculations. Germanium‐enriched: The synthesis and unusual chemical and electronic properties of the first zero‐valent germanium (“germylone”) iron complex [SiNSi]GeFe(CO)4 are reported. This complex was further transformed into an unprecedented mixed‐valent push–pull Ge0→GeCl2 complex.